Analisis Peran Sistem Informasi Produk Penyerapan Dana Pada Baitul Mal Wa Tamwil Mitra Utama - Oktaviani, Vika Rohma; Ansori, Miswan; Utami, Cahyaning Budi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to analyze the role of Sharia Savings and Loans Cooperatives (KSPPS) in improving the welfare of the Sinanggul community, Jepara. KSPPS plays an important role in providing access to sharia-based finance, which supports the development of the community's economy by avoiding the practices of usury, gharar, and maysir. Based on data from previous studies, KSPPS has been proven to have a significant impact on increasing community income and welfare, especially through the provision of financing for micro, small and medium enterprises (MSMEs). This study uses a descriptive qualitative method with a case study approach to explore more deeply how KSPPS in Sinanggul plays a role in supporting local economic development. The results of the study show that through sharia savings and financing products, KSPPS is able to increase financial inclusion and the economic welfare of the local community.